Continuing Education Need, Issues & Challenges in the Context of Technical Educational Institutions - Agnihotri, U. A.; Nathe, D. P. (Journal of Engineering Education Transformations, 2008)
This paper discusses the need and role of Continuing Education, its relevance in present environment. It also discusses the issues, approaches and challenges in the field of continuing education. Some aspects of strategic management and marketing issues related with continuing education are also discussed. The paper mainly emphasizes on the applications of managerial functions applied to continuing education considering it as " institute within the institute ". A case study is presented to share some efforts taken in the direction, which this paper advocates.